Unraveling the study of liquid smoke from rice husks as a green corrosion inhibitor in mild steel under 1 M HCl - Kaban, Agus; Mayangsari, Wahyu; Anwar, Mochammad; Maksum, Ahmad; Aditiyawarman, Taufik; Soedarsono, Johny; Ridhova, Aga; Riastuti, Rini (Eastern-European Journal of Enterprise Technologies, 2022)
The work provides the more comprehensive development of Liquid Smoke from Rice Husks Ash (RHA). Notably, the study focuses on the interaction between the primary molecules of inhibitor and mild steel, including thermodynamic calculation and surface treatment upon addition of inhibitor. The electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PP) characterization were utilized to evaluate the anticorrosion of RHA. The Raman Spectroscopy pre and post-addition of RHA’s inhibitor were used to compare the adsorbed functional group of inhibitors. Moreover, the thermodynamic calculation of the inhibitor’s adsorption determines the types of adsorption of the inhibitor. As a result of the adsorption process, the Scanning Electronic Microscope-Energy Dispersive X-Ray (SEM-EDX) aided by The Atomic Force Microscopy (AFM) and Contact Angle Test was implemented to unveil the surface treatment and the change of elemental composition after the addition of an 80 ppm inhibitor. The PP and EIS results show a significant depression of the current density at ‒2.75 μA·cm2 in 80 ppm solution with the highest inhibition efficiency of 99.82 %. The superior inhibition correlates to the adsorption of Si–OH, C–C, C–O–C, >C=O, complex structure, and –OH at wavenumber 458, 662, 1095, 1780, and 3530 cm-1. The LS shows a significant surface area of protection of 0.9982 and high adsorption constant (Kads) at 11.648. The calculated ΔGads of ‒6.59 kJ/mol unveils the chemisorption in nature. At the same time, a combination of 20 and 80 ppm solution is predicted adsorbed horizontally to reduce the contact between the solution and substrate, as shown in SEM and AFM results. It also increases the contact angle and their corresponding hydrophobicity